1996
DOI: 10.1046/j.1365-2249.1996.d01-863.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of recombinant granulocyte colony-stimulating factor (rhG-CSF) in experimental colitis

Abstract: SUMMARYInflammatory bowel disease is associated with mucosal neutrophil recruitment and activatation, mediated in part by arachidonic acid metabolites. G-CSF attenuates the immune response to sepsis and ameliorates glycogen storage disease Ib-related colitis. These actions may be effected through the shedding of neutrophil adhesion molecules, or inhibition of proinflammatory mediator synthesis. Immune complex colitis was used to evaluate the effect of rhG-CSF on colonic mucosal inflammation, neutrophil recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 24 publications
1
17
2
Order By: Relevance
“…Cytokine administration at either dose translated into increased tissue myeloperoxidase levels, despite a histologically similar mucosal polymorphonuclear cell infiltrate in the G-CSF-treated compared with the control colitis group. Moreover, dialysis fluid levels of leukotriene B4 and thromboxane B2 were significantly lower in treated animals (65). Similar results were obtained in the 2,4,6-trinitrobenzene sulfonic acid colitis in rats, a model of Th1 disease.…”
Section: G-csf In Inflammatory Bowel Diseasesupporting
confidence: 83%
See 1 more Smart Citation
“…Cytokine administration at either dose translated into increased tissue myeloperoxidase levels, despite a histologically similar mucosal polymorphonuclear cell infiltrate in the G-CSF-treated compared with the control colitis group. Moreover, dialysis fluid levels of leukotriene B4 and thromboxane B2 were significantly lower in treated animals (65). Similar results were obtained in the 2,4,6-trinitrobenzene sulfonic acid colitis in rats, a model of Th1 disease.…”
Section: G-csf In Inflammatory Bowel Diseasesupporting
confidence: 83%
“…G-CSF has been successfully used in experimental colitis in White New Zealand rabbits (65). Animals were pretreated either 24 h before or at colitis induction either with 50 or 200 g/kg rG-CSF.…”
Section: G-csf In Inflammatory Bowel Diseasementioning
confidence: 99%
“…Dieckgraefe et al showed that the administration of GM-CSF, a potent stimulant for hematopoiesis, was effective for treating patients with active CD (38). These results in humans were supported by the results of animal studies demonstrating that bone marrow cells (39,40) or their inducers (41,42) could ameliorate experimental colitis.…”
Section: Photomicrograph Of a Typical Colony-forming Units Represenmentioning
confidence: 74%
“…In fact, administration of G-CSF has been shown to ameliorate colonic inflammation in animal models of colitis, 28,27 and be a safe and effective biologic agent for the treatment of active CD. 29 In this study, we have shown that G-CSF was highly expressed in noninflamed regions of both mouse and human intestinal lamina propria.…”
Section: Discussionmentioning
confidence: 99%
“…These effects include the suppression of proinflammatory cytokine production, 20 -23 and promotion of the generation of regulatory antigen presenting cells, 24 regulatory T (Treg) cells, 25 and Th2 cells. 22,26 Studies have also shown that G-CSF treatment is effective in ameliorating bowel inflammation in animal colitis models 27,28 and preclinical trials. 29,30 Although the immunomodulatory roles of G-CSF have been demonstrated, its role in maintaining immunological homeostasis in the intestine has not yet been addressed.…”
mentioning
confidence: 99%